Formal conditions in imposition of disciplinary penalties in the DisciplinaryCode state and public sector employees NO (14) for the year (1991) amended - Abdullah Hamza, Badrkhan (Zanco Journal of Human Sciences, 2023)
According to Iraqi Law of Discipline of State Employees and the Public Sector No (14) for the year (1991), several formality procedures should be observed during the imposition of disciplinary penalty. These procedures are multifaceted; the most important of which is that the decision to impose the punishment must have effects and be based on evidence and be issued by an impartial authority. And at the same time, the litigants to the case must have the right to appeal according to the aforementioned law. Failure to observe these procedural requirements renders the annulment by the administrative administrative decision related to imposing the punishment flawed, which requires its court. Formal conditions, disciplinary penalties, administrative investigation, interrogation, state and public sector employee discipline law. Kurdistan